Hukuman Terhadap Koruptor dalam Perspektif Hukum Islam - Wahid, Saenal (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
The purpose of this study was to know the punishment for corruptors in the perspective of Islamic law. The type of research was qualitative research based on library research. The results showed that the forms of violation of the law of corruption in Indonesia in the perspective of Islamic law can be in the form of ghulul (treason), al-ghasy (fraud), and risywah (bribery), al-hirabah (exploitation), and al-ghasab (use of the rights of others without permission). The elements of criminal acts of corruption in the perspective of Islamic Criminal Law are the existence of texts that prohibit it, then having committed acts that have violated the texts, for example committing khiyanah/ghulul, al-ghasy (fraud), risywah (bribery), al-hirabah (deprivation), al-ghasab (use of other people's rights without permission), and finally the perpetrators are people who can be charged with law. The punishment for corruptors in the context of Islamic Criminal Law can be in the form of takzir, moral sanctions, social sanctions and sanctions of the afterlife.